Pengaruh Pemberian Tepung Kayu Manis (Cinnamomum Burmanii) Dalam Ransum Terhadap Bobot Karkas dan Persentase Karkas Itik Pedaging: Effect of Cinnamon Powder (Cinnamomum burmannii) in The Ration on Carcass Weight and Carcass Percentage of Broiler Duck - Irmayani; Hikmah Daming; Nevyani Asikin; Munir Munir; Fitriani Fitriani (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the effect of giving cinnamon flour in the ration to the carcass percentage and carcass weight of broiler ducks. This research was conducted in September-October 2021, Maritengae sub-district, Sidrap Regency. The design model used in this study was a completely randomized design (CRD) consisting of 4 treatments and 3 replications so that there were 12 units of observation and where each unit consisted of 5 birds so that a total of 60 observations were made. The feed was arranged according to the nutritional needs of the ducks. The treatments were: P0: No control treatment 0%, P1: Cinnamon bark flour 1% of the total feed, P2: Cinnamon bark flour 3% of the total feed and P3: Cinnamon bark flour 5% of the total feed. The results showed that the addition of Cinnamon (Cinnamomum burmanii) flour to quail feed had no significant effect (P>0.05) on carcass weight, while the addition of Cinnamomum (Cinnamomum burmanii) flour to quail feed had no significant effect (P>0.05). to the carcass percentage.